Conjoint Analysis in Consumer Research: Issues and Outlook - Green, Paul E.; Srinivasan, V. (Journal of Consumer Research, 1978)
Abstract Since 1971 conjoint analysis has been applied to a wide variety of problems in consumer research. This paper discusses various issues involved in implementing conjoint analysis and describes some new technical developments and application areas for the methodology.